Hotel Employee Performance Review: The Effect of Job Satisfaction, Competence and Motivation - Susmono Widagdo; Mariatul Qibtiyah; Eni Rahayu; Henry Yuliamir; Dyah Palupiningtyas (Pusat Riset dan Inovasi Nasional, 2022)
Companies must always foster employee motivation through the fulfillment of the basic physiological needs of employees, security, social needs, esteem and opportunities for self-actualization. This study aims to prove the effects of competence and motivation on job satisfaction and their impact on employee performance at Sahid Jaya Solo Hotel. This research is included in quantitative research using SPSS 16 and research design using associative approach. The associative approach was carried out with the aim of finding the effect of compensation and work environment on performance mediated by work motivation. . Collecting data using research instruments, data analysis is quantitative or statistical, with the aim of testing the established hypothesis. The place of this research is Sahid Jaya Hotel Solo, Jalan Gajah Mada No.82, Ketelan, Banjarsari, Surakarta City, Central Java 57132. This research was conducted for 6 months starting from May 2017 and is estimated to be completed in October 2017. The population that the author uses as the object of this research is the employees at Hotel Sahid Jaya Solo. The number of employees at Hotel Sahid Jaya Solo is 114 employees. The results show that there are positive significant effects of competence and motivation on job satisfaction and their impact on employee performance at Sahid Jaya Solo Hotel.